Case report: Total thoracoscopic repair of sinus of Valsalva aneurysm combined with ventricular septal defect - Tan, Tong; Liu, Haozhong; Ma, Jianrui; Liu, Jian; Yuan, Haiyun; Guo, Huiming (Frontiers in Cardiovascular Medicine, 2022)
The sinus of Valsalva aneurysm (SVA) is a rare cardiac anomaly. It can develop into the heart failure if it ruptures, which requires early intervention. However, such congenital anomalies are usually treated using a median sternotomy approach. Here, we report a rare case of SVA combined with a ventricular septal defect in which the patient underwent patch repair of the defects under a total thoracoscopy approach. She was discharged uneventfully and showed no residual shunt or aortic regurgitation postoperatively or at the 12-month follow-up. The total thoracoscopic approach for SVA repair is technically feasible.